Decellularized esophageal tubular scaffold microperforated by quantum molecular resonance technology and seeded with mesenchymal stromal cells for tissue engineering esophageal regeneration - Marzaro, Maurizio; Pozzato, Gianantonio; Tedesco, Stefano; Algeri, Mattia; Pozzato, Alessandro; Tomao, Luigi; Montano, Ilaria; Torroni, Filippo; Balassone, Valerio; Contini, Anna Chiara Iolanda; Guerra, Luciano; D’Angelo, Tommaso; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Current surgical options for patients requiring esophageal replacement suffer from several limitations and do not assure a satisfactory quality of life. Tissue engineering techniques for the creation of customized “self-developing” esophageal substitutes, which are obtained by seeding autologous cells on artificial or natural scaffolds, allow simplifying surgical procedures and achieving good clinical outcomes. In this context, an appealing approach is based on the exploitation of decellularized tissues as biological matrices to be colonized by the appropriate cell types to regenerate the desired organs. With specific regard to the esophagus, the presence of a thick connective texture in the decellularized scaffold hampers an adequate penetration and spatial distribution of cells. In the present work, the Quantum Molecular Resonance® (QMR) technology was used to create a regular microchannel structure inside the connective tissue of full-thickness decellularized tubular porcine esophagi to facilitate a diffuse and uniform spreading of seeded mesenchymal stromal cells within the scaffold. Esophageal samples were thoroughly characterized before and after decellularization and microperforation in terms of residual DNA content, matrix composition, structure and biomechanical features. The scaffold was seeded with mesenchymal stromal cells under dynamic conditions, to assess the ability to be repopulated before its implantation in a large animal model. At the end of the procedure, they resemble the original esophagus, preserving the characteristic multilayer composition and maintaining biomechanical properties adequate for surgery. After the sacrifice we had histological and immunohistochemical evidence of the full-thickness regeneration of the esophageal wall, resembling the native organ. These results suggest the QMR microperforated decellularized esophageal scaffold as a promising device for esophagus regeneration in patients needing esophageal substitution.